(untitled) (Estudios Sociales, 2023)
The process of building social policies was not an exclusive note of Mendoza, but is related to national and international vicissitudes, although it received a decisive boost during the lencinistas times, positioning it as a pioneer in social matters. In this framework, this work aimed to rescue the processes of consensus and conflict at the time of chiselling social policies within the Legislature, aiming to recover the voices of political actors to account for the political, social and economic visions that were maintained by the different political forces, the encounters and disagreements about the state role and the incidence of the trajectories and knowledge of some specific figures in their design. Despite the postwar reformist consensus, politicians engaged in disputes over the limits of state penetration and the foundations of representative, republican, and federal rule.